CONNECTEDNESS OF INVERSE LIMIT OF GENERALIZED TOPOLOGICAL SPACES - Lončar, Ivan (Matematichki Bilten, 2019)
The aim of this paper is to study the connectednes of inverse limit of generalized topological spaces introduced by Császár in [3].